Awareness of risk factors for coronary heart disease in patients after myocardial infarction - Katarzyna Sawicka; Alicja Grządka; Robert Łuczyk; Agnieszka Wawryniuk; Marek Prasał; Marta Łuczyk; Jadwiga Daniluk (Kazimierz Wielki University, 2016)
Admission. Cardiovascular diseases are the leading cause of morbidity and mortality both in Poland and in the world. According to the World Health Organization (WHO) mortality due to coronary heart disease will increase in 2020 to 11.1 million. These statistics show that this is an important health problem. The aim of the study is to determine the level of awareness of the risk factors for coronary heart disease in patients after myocardial infarction. Materials and methods of research. The survey was conducted from February to April 2016. The study group consisted of persons after myocardial infarction, from 42 - 87 years of age. Respondents wishing to participate in the study were given a battery of tests consisting of a questionnaire author. The survey contained 30 questions and imprint (gender, age, height, weight, place of residence, education, duration of ischemic heart disease, the time elapsed since the last attack). The results were statistically analyzed. The values of the analyzed parameters measurable shown by the mean, median, minimum and maximum values and standard deviation, and the immeasurable using the frequencies and percentage. Conclusions. 1. Patients after myocardial infarction have little knowledge about the risk factors for coronary heart disease. 2. Respondents not able to identify modifiable and non-modifiable risk factors for coronary heart disease. 3. Education has an impact on the level of awareness of risk factors for coronary heart disease. People with higher and secondary education have a greater awareness of the risk factors of coronary heart disease than those with primary education. Sex, age, place of residence, disease duration, the time elapsed since the last attack did not affect the level of awareness of the risk factors for coronary heart disease. 4. The level of awareness of risk factors for coronary heart disease does not affect the everyday behavior of patients.